Pundukdawa Movement: In Search of Identity, Deconstructing Ideology of Hierarchy in Contemporary Bali - I Gde Pitana (Universitas Udayana, 2025)
Contestations related to hierarchy among the Balinese have long been discussed. In present-day Bali, one of the most spectacular cases of hierarchical conflict was the conflict surrounding the prohibition of a high priest from Wangsa Pasek (Pasek Maxima Clan) from officiating rituals in Pura Dasar Bhuana in Gelgel, Klungkung. This conflict triggered the construction of a new temple, called Pura Catur Parhyangan Ratu Pasek Linggih Ida Bethara Mpu Ghana located in Pundukdawa village, also in Klungkung district. This research aimed to analyse in depth the motivation of the temple construction and its ramifications, employing a qualitative research approach. It concluded that the development of the new temple is a movement to search and strengthen identity (wangsa identity, identitas ke-wangsa-an), and to increase the maxima clan’s standing. The findings of this research suggest that in analysing the current hierarchy and dominance in Balinese society, it can no longer employ analytical theories based on static hierarchy.